Study of the antioxidant potential, polyphenol content, and mineral composition of Cordyla pinnata, a plant for food and medicinal use of the Senegalese pharmacopoeia - Dieye, Pape Issakha; Wane, Thierno Mouhamed; Faye, Elhadj Ousmane; Gueye, Rokhaya; Diop, Amadou; Ndiaye, Bara; Diop, Yerim Mbagnick; Sarr, Serigne Omar (European Journal of Chemistry, 2022)
Oxidative stress, caused by reactive oxygen species, is known to cause oxidation of biomolecules, leading to cell damage and oxidation of important enzymes, resulting in an unstable pathophysiological state. The antioxidant capacity of leaves, stems, and roots of Cordyla pinnata was determined by measuring the inhibition of the absorbance of 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and 2,2’-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicals by spectrophotometry. The polyphenol contents were determined with the same technique. The mineral contents were evaluated by atomic absorption spectrometry. The strongest inhibition of the DPPH radical after that of the control antioxidant (IC50 = 0.014 mg/mL) was obtained with the ethyl acetate fraction of the leaf hydroethanolic extract (IC50 = 0.201 mg/mL). For ABTS, the ethyl acetate fraction of the stem extract was more active (IC50 = 0.884×10-3 mg/mL) than the other extracts and ascorbic acid (IC50 = 0.915×10-3 mg/mL). The polyphenol content of the leaves, stems and roots extracts is between 66.33 and 142.67; 55.33 and 69.33; 67.67 and 116.00 EAT/g of dry extract, respectively. The contents of Fe, Na, Zn, K, Mg, and Ca are 0.0005, 0.0006, 0.0020, 0.0897, 0.0247, and 0.0273% for leaves, respectively. They are 0.0001, 0.0010, 0.0015, 0.0557, 0.0131, and 0.1357% for the stems, respectively. The mineral contents of the roots in the same order are 0.0002, 0.0013, 0.0013, 0.0140, 0.0096, and 0.0267%. Strong inhibition of free radicals and the chemical composition of various plant materials would justify the use of C. pinnata in the management of certain pathologies and nutritional deficiencies.